"They just have more of a vibe of being 'one of us'": undergraduate law student perceptions of PhD tutors. Issue 3 (2nd July 2020) - Ball, Victoria; Joyce, Arwen; Mills, Charlotte
ABSTRACT: This study examines undergraduate law students' perceptions of tutorials delivered by PhD tutors. Enrolment in UK law schools has increased in recent decades and PhD tutors are playing an ever-expanding pedagogical role in undergraduate degree courses. At the same time, the implementation of the Teaching Excellence and Student Outcomes Framework and the growing credence given to the results of the National Student Survey have increased UK universities' focus on achieving consistently high teaching standards and improving the student experience. This makes a study seeking to ascertain undergraduate law students' perceptions of PhD tutors timely and relevant. The empirical data collected via a questionnaire and then mapped against the existing pedagogical literature on effective teaching reveals students' generally favourable view of PhD tutors and bolsters the view that PhD tutors are engaging in effective teaching practices. The respondents indicated that, in their experience, PhD tutors communicate clearly, employ novel teaching techniques, help them prepare for exams and set high academic expectations while being enthusiastic, approachable and relatable. While this research primarily draws on the experience of law students at the University of Leicester, the findings are applicable to similar institutions and to all current PhD tutors and PhD students who are considering teaching.